An SiO Toroid and Wide-angle Outflow Associated with the Massive Protostar W75N(B)-VLA2 - Gómez Gallardo, José Facundo (2023)
We have carried out Atacama Large Millimeter/submillimeter Array observations of the massive star-forming region W75N(B), which contains the massive protostars VLA1, VLA2, and VLA3. Particularly, VLA2 is an enigmatic protostar associated with a wind-driven H2O maser shell, which has evolved from an almost isotropic outflow to a collimated one in just 20 yr. The shell expansion seemed to be halted by an obstacle located to the northeast of VLA2. Here we present our findings from observing the 1.3 mm continuum and H2CO and SiO emission lines. Within a region of ~30″ (~39,000 au) diameter, we have detected 40 compact millimeter continuum sources, three of them coinciding with VLA1, VLA2, and VLA3. While the H2CO emission is mainly distributed in a fragmented structure around the three massive protostars, but without any of the main H2CO clumps spatially coinciding with them, the SiO is highly concentrated on VLA2, indicating the presence of very strong shocks generated near this protostar. The SiO emission is clearly resolved into an elongated structure (~0.″6 × 0.″3; ~780 au×390 au) perpendicular to the major axis of the wind-driven maser shell. The structure and kinematics of the SiO emission are consistent with a toroid and a wide-angle outflow surrounding a central mass of ~10 M ⊙, thus supporting previous theoretical predictions regarding the evolution of the outflow. Additionally, we have identified the expected location and estimated the gas density of the obstacle that is hindering the expansion of the maser shell.